Spinal pain prevalence in Wales and associated risk factors. - Hywel Turner Evans; Ian Farr; David Byfield; Benjamin Stacey; Damian Bailey (International Journal of Population Data Science, 2022)
Objectives Spinal pain predisposes patients to a more sedentary lifestyle, a major risk factor for cardiovascular disease and other comorbidities. There is little recent evidence of the current prevalence of spinal pain and associated risk factors in Wales. This analysis addresses this gap in knowledge.